2019
DOI: 10.1007/s11095-019-2720-6
|View full text |Cite|
|
Sign up to set email alerts
|

High Content Solid Dispersions for Dose Window Extension: A Basis for Design Flexibility in Fused Deposition Modelling

Abstract: PurposeThis study uses high drug content solid dispersions for dose window extension beyond current demonstrations using fused deposition modelling (FDM) to; i) accommodate pharmaceutically relevant doses of drugs of varying potencies at acceptable dosage form sizes and ii) enable enhanced dose flexibility via modular dosage form design concepts.MethodsFDM was used to generate ~0.5 mm thick discs of varying diameter (2–10 mm) from melt-extruded feedstocks based on 10% to 50% w/w felodipine in ethyl cellulose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…3D-printed systems containing poorly soluble drugs have been examined; however, the stability of these formulations has not been evaluated thoroughly. In a recent study, Govender et al examined this issue, showing good stability with high percentages of drug incorporation, albeit with a polymer insoluble in water [43]. It has also been demonstrated that amorphization via hot-melt extrusion and subsequent FDM can produce formulations in which the drug quickly recrystallizes [44].…”
Section: Introductionmentioning
confidence: 99%
“…3D-printed systems containing poorly soluble drugs have been examined; however, the stability of these formulations has not been evaluated thoroughly. In a recent study, Govender et al examined this issue, showing good stability with high percentages of drug incorporation, albeit with a polymer insoluble in water [43]. It has also been demonstrated that amorphization via hot-melt extrusion and subsequent FDM can produce formulations in which the drug quickly recrystallizes [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, the final target orifice diameter for the MV3 constructs used in subsequent drug release testing was 0.8 mm. Previous studies have shown that FDM dispensing precision decreases with dispensing volume [ 70 ]. It can therefore be concluded that larger feature sizes are expected to be generated with higher precision during FDM.…”
Section: Resultsmentioning
confidence: 99%
“…Identical doses within individual module variants, if desired, could have been achieved through overfilling of MV1 and MV2 cores to match overfilling of MV3 cores. Alternatively, achieving scalable individualized dosing with modular dosage form design concepts at a fixed dosage form size was already addressed in our previous work [ 70 ]. As described above, maintaining acceptable dosage form sizes independent of the dose strength requires modules that are a fraction of the size of a conventional dosage form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these modular product designs, cost and benefit studies were conducted. Govender et al [9] and Govender et al [10] experimentally showed the realization of a modular product design for a pharmaceutical product with a scalable dose strength and flexible, but controlled, target release profile. Building on the studies by Siiskonen et al [8], Govender et al [9], and Govender et al [10], the novelty of this paper is a theoretical modeling approach to generate modular product designs for pharmaceutical products for cost-efficient customization.…”
Section: Introductionmentioning
confidence: 99%